2020
DOI: 10.1044/2019_jslhr-19-00210
|View full text |Cite
|
Sign up to set email alerts
|

Language and Inhibition: Predictive Relationships in Children With Language Impairment Relative to Typically Developing Peers

Abstract: Background This study examined predictive relationships between two indices of language—receptive vocabulary and morphological comprehension—and inhibition in children with specific language impairment (SLI) and typically developing (TD) children. Methods Participants included 30 children with SLI and 41 TD age-matched peers (8–12 years). At two time points separated by 1 year, we assessed receptive vocabulary and morphological comprehension via standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…The posterior distribution, therefore, includes information from prior literature directly in the results. As is common under a Bayesian framework (e.g., Larson et al, 2020 ), we interpreted an effect to be important if zero was not contained within the 95% PPI and we used the term “important” to identify these effects. See Supplementary Materials 2 for all model convergence information which describes the model fit of the model predictions with the data.…”
Section: Methodsmentioning
confidence: 99%
“…The posterior distribution, therefore, includes information from prior literature directly in the results. As is common under a Bayesian framework (e.g., Larson et al, 2020 ), we interpreted an effect to be important if zero was not contained within the 95% PPI and we used the term “important” to identify these effects. See Supplementary Materials 2 for all model convergence information which describes the model fit of the model predictions with the data.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in monolingual children have shown evidence of both unidirectional and bidirectional relations between language and executive function (including inhibitory control). While some authors suggest that executive function comes first and predicts language outcomes (e.g., Weiland et al, 2014 ; White et al, 2017 ; Ekerim and Selcuk, 2018 ; Larson et al, 2020 ) others suggest just the opposite, that language ability comes first and predicts inhibitory control (e.g., Fuhs and Day, 2011 ; Kuhn et al, 2016 ; Botting et al, 2017 ). Bidirectional relations have been also reported in previous studies in which language and executive function influence each other equally (e.g., Kaefer and Neuman, 2013 ; Bohlmann et al, 2015 ; Slot and von Suchodoletz, 2018 ).…”
Section: Relation Between Inhibitory Control and Languagementioning
confidence: 99%
“…The precise mechanisms behind its causation is unknown and recent research indicates both verbal and nonverbal skills are implicated (Conti-Ramsden et al, 2012). An increasing body of research suggests that the development of inhibition and language are interdependent (Kohnert, 2008; Spaulding, 2010) and compared to typically developing children, many children with DLD have difficulty with inhibition (Larson et al, 2020). Given the importance of the early identification of children with DLD, understanding the early development of inhibition in children at risk of DLD is needed.…”
mentioning
confidence: 99%
“…Research has shown that a child who has problems with inhibition, is also likely to have problems with receptive and/or expressive language (Russell et al, 1999). Recently, Larson et al (2020) found predictive relationships between inhibition and aspects of language (morphology) and suggested that targeting inhibition skills in children with DLD is likely to improve morphological comprehension. However, these studies have not included bilingual children and there are few studies examining response inhibition in preschool children with DLD.…”
mentioning
confidence: 99%
See 1 more Smart Citation